2018
DOI: 10.1093/cercor/bhy116
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Dynamic Modulations That Underpin a Resilient Neural Network for Semantic Cognition: An fMRI Investigation in Patients With Anterior Temporal Lobe Resection

Abstract: One critical feature of any well-engineered system is its resilience to perturbation and minor damage. The purpose of the current study was to investigate how resilience is achieved in higher cognitive systems, which we explored through the domain of semantic cognition. Convergent evidence implicates the bilateral anterior temporal lobes (ATLs) as a conceptual knowledge hub. While bilateral damage to this region produces profound semantic impairment, unilateral atrophy/resection or transient perturbation has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 59 publications
9
39
0
Order By: Relevance
“…with previous research, lexical processing activated left supramarginal gyrus, fronto-central and middle temporal brain areas, which have been argued to support lexical-semantic processing of words (Fig 2A, 3A) (46,54,32,47,51). 'Mere' syllable transition processing, in contrast, activated fronto-centro-temporal brain areas in both hemispheres ( Fig 2B, 3B).…”
Section: Lexical and Syllable Transition Processing Of Words Activatesupporting
confidence: 75%
See 1 more Smart Citation
“…with previous research, lexical processing activated left supramarginal gyrus, fronto-central and middle temporal brain areas, which have been argued to support lexical-semantic processing of words (Fig 2A, 3A) (46,54,32,47,51). 'Mere' syllable transition processing, in contrast, activated fronto-centro-temporal brain areas in both hemispheres ( Fig 2B, 3B).…”
Section: Lexical and Syllable Transition Processing Of Words Activatesupporting
confidence: 75%
“…That being said, the posterior MTG (perhaps left lateralized (44)) has been suggested to provide a sound-to-meaning interface for the mapping of phonological representations in STS to lexical representations (45,46,44,47,48). Lexical-semantic compositional processing as well as sentence level processing additionally has been shown to activate the anterior temporal lobe (ATL) (49)(50)(51). Sublexical contingencies, such as syllable transitions, contribute to word processing, and have been shown to activate parts of the STS (52,53) and a dorsal-path network (54).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we found that semantically-demanding conditions upregulated the left-lateralized semantic regions including the vATL, IFG and pMTG as well as other regions in domain general networks. More specifically, there was increased activation in the bilateral ATL supporting the notion that semantic representation is inherently bilateral in nature (1,31,42). Functional connectivity between these regions (interhemispheric vATL connectivity and the vATL-PFC) was also increased.…”
Section: Discussionsupporting
confidence: 54%
“…We manipulated task difficulty in two different ways: stimulus manipulation (SM) and response time manipulation (RM) (Fig.1). The RM data have been reported in a recent examination of the semantic network in patients with ATL resection (31).…”
Section: Experimental Designmentioning
confidence: 85%
See 1 more Smart Citation